The town of N - Dobychin, Leonid (European classics (Evanston, Ill.), 1998)
Leonid Dobychin's The Town of N, an unrecognized masterpiece of the Soviet 1930s, virtually vanished, together with its author, following its publication in 1935 and the subsequent vilification of Dobychin by Leningrad's cultural authorities. Now, more than half a century later, this short masterpiece has been rediscovered, first in Russia in 1989, and now in this first English translation.